Impact of Accountability and Transparency On ZIS Fund Management : A Case Study of BAZNAS Sidoarjo Regency - Shinta Aliyah Putri; Munari Munari (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose : This study aims to determine and empirically test the relationship between accountability and transparency in the management of ZIS funds. Method: The research uses a quantitative method with a questionnaire distributed to employees as respondents. The data collected were analyzed using multiple linear regression to test the hypothesis. Results: The results show that the implementation of the Accountability Anda Transparency  have a positive and significant effect on management of ZIS funds, both partially and simultaneously. Findings: High accountability and transparency are very important in increasing the effectiveness of ZIS fund management, both in terms of public trust, governance, and institutional accountability. Novelty: This study provides a contextual analysis of how accountability and transparency factors affect the management of ZIS funds in related management institutions. Originality: Unlike previous studies, this research specifically focuses on BASNAZ Sidaorjo Regency and uses SPSS analysis to assess the performance of related institutions in managing ZIS funds. Conclusion: The implementation of accountability and transparency plays an important role in improving institutional performance. The findings provide valuable implications for other organizations working in the same field. Type of Paper: Research Paper